THE SIGNIFICANCE OF INNOVATIVE DEVELOPMENT IN SCIENCE AND EDUCATION - Sherkulova N.R.; Hamidova I.O.; Eliboyeva M.Sh. (Bright Mind Publishing, 2025)
This article discusses the theoretical views on the role and importance of innovative development in the development of science and education.
Keywords: education, innovative, science, development, technique, technology, fundamental, theoretical, practical, integration, strategy